Essential Role for CD30-Transglutaminase 2 Axis in Memory Th1 and Th17 Cell Generation - Suzuki, Akane S.; Yagi, Ryoji; Kimura, Motoko Y.; Iwamura, Chiaki; Shinoda, Kenta; Onodera, Atsushi; Hirahara, Kiyoshi; Tumes, Damon J.; Koyama-Nasu, Ryo; Iismaa, Siiri E.; Graham, Robert M.; Motohashi, Shinichiro; et al. (Frontiers in Immunology, 2020)
Memory helper T (Th) cells are crucial for secondary immune responses against infectious microorganisms but also drive the pathogenesis of chronic inflammatory diseases. Therefore, it is of fundamental importance to understand how memory T cells are generated. However, the molecular mechanisms governing memory Th cell generation remain incompletely understood. Here, we identified CD30 as a molecule heterogeneously expressed on effector Th1 and Th17 cells, and CD30hi effector Th1 and Th17 cells preferentially generated memory Th1 and Th17 cells. We found that CD30 mediated signal induced Transglutaminase-2 (TG2) expression, and that the TG2 expression in effector Th cells is essential for memory Th cell generation. In fact, Cd30-deficiency resulted in the impaired generation of memory Th1 and Th17 cells, which can be rescued by overexpression of TG2. Furthermore, transglutaminase-2 (Tgm2)-deficient CD4 T cells failed to become memory Th cells. As a result, T cells from Tgm2-deficient mice displayed impaired antigen-specific antibody production and attenuated Th17-mediated allergic responses. Our data indicate that CD30-induced TG2 expression in effector Th cells is essential for the generation of memory Th1 and Th17 cells, and that CD30 can be a marker for precursors of memory Th1 and Th17 cells.